Effect of Massage, Soak Feet Warm Water, and Aromatherapy for Decreasing Blood Pressure in Older Adults with Hypertension: A Literature Review - Emmalia Adhi Fitama; Joni Haryanto; Makhfudli Makhfudli (Universitas Airlangga, 2021)
Introduction: The increase in blood pressure that lasts long enough to cause damage to the kidneys, heart, and brain. This is in line with Carol A. Miller's theory regarding the aging process that occurs in the older adults. Miller's functional theory in the development process, the older adults will experience many changes, one of which is the dilated and stiff arteries, this results in reduced vascular recoil capacity. The purpose of this study was to determine the effect of massage, warm water foot soaking, and aromatherapy on lowering blood pressure in hypertensive older adults based on empirical studies of the last ten years.Method: Search for journals or articles using a database through Scopus, ProQuest, PubMed, SAGE, EBSCO, Scient Direct, Research Gate, and Google Scholar. The Center for Review and Dissemination and The Joanna Briggs Institute were used to assess the study's quality. The framework used for the review is PICOS, and the inclusion criteria used are English and Indonesian language journals with a coverage of the last ten years, older adults who lives in nursing home or community older adults, outcomes: decreased to blood pressure, and the study design of quasy-experimental studies, randomized control and trial, qualitative research and cross-sectional studies.Result: After screening twenty-five article, but only Thirteen studies matched the research criteria. Six studies suggest that age is a significant factor in hypertension and seven studies the presence of excess sympathetic activity. Meanwhile, strategies to reduce blood pressure in the older adults include massage, soaking feet in warm water, and aromatherapy.Conclusion: Decreased prevalence of hypertension in the older adults can be carried out pharmacologically and non-pharmacologically. The strategy is entirely sufficient for lowering blood pressure in elderly hypertensive are massage, foot soak warm water, and aromatherapy as inhaled a calming effect. Determines successfully in complementary therapy in lowering blood pressure.